2002
DOI: 10.1007/s003940200010
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia, and low intakes of folic acid and vitamin B12 in urban North India

Abstract: Low intakes of folic acid and vitamin B12, and hyperhomocysteinemia, in both the healthy population living in urban slums and adjacent urban non-slum areas, are important observations for the prevention of nutritional and cardiovascular diseases in the Indian subcontinent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
68
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 37 publications
7
68
3
Order By: Relevance
“…Vegetarians are more likely to be deficient in vitamin B6, vitamin B 12 , and folate which are the essential cofactors for homocysteine metabolism. Recent evidence strongly suggests that too little vitamin B 12 can lead to high level of homocysteine [28][29][30][31][32][33]. In our study, we have seen that weight and alcohol intake are statistically significant predictors of homocysteine (P = 0.006 and P = 0.036, respectively).…”
Section: Discussionsupporting
confidence: 57%
“…Vegetarians are more likely to be deficient in vitamin B6, vitamin B 12 , and folate which are the essential cofactors for homocysteine metabolism. Recent evidence strongly suggests that too little vitamin B 12 can lead to high level of homocysteine [28][29][30][31][32][33]. In our study, we have seen that weight and alcohol intake are statistically significant predictors of homocysteine (P = 0.006 and P = 0.036, respectively).…”
Section: Discussionsupporting
confidence: 57%
“…For example, a study in adult slum dwellers in New Delhi, India, found that 93% had folate intakes below the Indian recommended daily allowances (RDAs). 4 Many children in LMICs have suboptimal or poor status of either or both of these nutrients. 5 However, to what extent this situation has any consequences for their health and growth is not clear.…”
mentioning
confidence: 99%
“…[20][21][22] The mean homocysteine levels too are quite high, varying from 19.5 to 23.2 µmol/L. [20,21] Our study on Western Rajasthan subjects has also revealed a very high mean homocysteine of 34.79 micromole/litre in case group.…”
Section: Discussionmentioning
confidence: 90%